Consistent practices in pressure ulcer prevention based on international care guidelines: A cross-sectional study - Haavisto Elina; Stolt Minna; Puukka Pauli; Korhonen Teija; Kielo-Viljamaa Emilia (WILEY, 2022)
The use of consistent and evidence-based practices is essential in terms of patient safety and quality of care. The purpose of this study was to describe the use of consistent practices in PU prevention based on international care guidelines and to assess the validity and reliability of the pressure ulcer prevention practice (PUPreP) instrument. The data (n = 554) were collected between 2018 and 2019 from nursing professionals working at two hospital districts in Finland using the PUPreP instrument. The instrument consisted of 42 items assessing participants' perceptions of the frequencies of pressure ulcer prevention practices with the following scale: never, sometimes, often, always. The data were analysed using statistical analysis. According to the results, the use of pressure ulcer prevention practices was more frequently described as often. The most frequently used prevention practice was repositioning, and the least frequently used practice was nutrition. Factors related to nursing professionals' pressure ulcer prevention practices were the working sector, education and working frequency in pressure ulcer prevention, and early identification of pressure ulcers. The study results suggest that the evidence-based pressure ulcer prevention practices were followed at a moderate level by nurses. The PuPreP instrument demonstrated validity and reliability, but further development is needed.